Systematic Review on Food Safety and Supply Chain Risk Assessment Post Pandemic: Malaysian Perspective - Nurul Eiman, Md Saad; Aida, Firdaus Muhammad Nurul Azmi; Mahmudiono, Trias; Raseetha, Siva (Frontiers in Sustainable Food Systems, 2021)
The novel coronavirus disease 2019, or Covid-19, is a recent disease that has struck the entire world. This review is conducted to study the impacts of the Covid-19 pandemic to food safety as well as the food supply chain. The pandemic has caused various changes around the world as numerous countries and governments have implemented lockdowns and restrictions to help curb the rising cases due to Covid-19. However, these restrictions have impacted many aspects of everyday life, including the economic sectors such as the food industry. An overview of the current Covid-19 situation in Malaysia was discussed in this review along with its implication on food safety and food supply chain. This is followed by a discussion on the definition of food safety, the impact of the pandemic to food safety, as well as the steps to be taken to ensure food safety. Hygiene of food handlers, complete vaccination requirement, kitchen sanitation and strict standard operating procedures (SOPs) should be in place to ensure the safety of food products, either in food industries or small scale business. Additionally, the aspect of the food supply chain was also discussed, including the definition of the food supply chain and the impact of Covid-19 to the food supply chain. Travel restriction and lack of manpower had impacted the usual operation and production activities. Lack of customers and financial difficulties to sustain business operational costs had even resulted in business closure. As a conclusion, this article provides insight into crucial factors that need to be considered to effectively contain Covid-19 cases and highlights the precaution methods to be taken through continuous monitoring and implementation by Malaysian government.